2019
DOI: 10.1152/ajpregu.00006.2018
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analytic insights into factors influencing the repeatability of hormone levels in agricultural, ecological, and medical fields

Abstract: Interest in individual variation in hormone concentrations is rapidly increasing, particularly with regard to the evolutionary and practical implications. A key aspect of studying individual variation in any labile trait is estimating the degree of within- versus among-individual variation, but at present, we do not have a broad consensus on the extent to which hormone levels are repeatable and what factors might influence repeatability. To address this knowledge gap, we conducted a comprehensive meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
5
9
0
Order By: Relevance
“…Cortisol responsiveness was significantly repeatable at both sampling times (1 and 2 h after being placed in a novel environment), but baseline cortisol was not repeatable. Despite the low sample size of the current study (N = 12 individuals), this result is consistent with recent meta-analyses [ 28 , 30 , 31 ] as well as current research with male guinea pigs [ 29 , 37 ] that consistently find cortisol responsiveness to be more repeatable than baseline cortisol. Repeatability is calculated as the proportion of total phenotypic variance that is attributed to the between-individual component, and decomposing variance into the within- and between-individual components aids in understanding why measurements differ in repeatability [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Cortisol responsiveness was significantly repeatable at both sampling times (1 and 2 h after being placed in a novel environment), but baseline cortisol was not repeatable. Despite the low sample size of the current study (N = 12 individuals), this result is consistent with recent meta-analyses [ 28 , 30 , 31 ] as well as current research with male guinea pigs [ 29 , 37 ] that consistently find cortisol responsiveness to be more repeatable than baseline cortisol. Repeatability is calculated as the proportion of total phenotypic variance that is attributed to the between-individual component, and decomposing variance into the within- and between-individual components aids in understanding why measurements differ in repeatability [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Historically, female behavior has been dismissed as less stable due to the influence of reproductive state [ 25 ], although recent studies have shown that female behavior is at least as stable as male behavior [ 26 , 27 ]. Recent work has also demonstrated that hormonal patterns can be temporally stable [ 28 31 ]. Specifically, testosterone and cortisol responsiveness are repeatable, but results are inconclusive on the repeatability of baseline cortisol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…distinct trait‐specific SRN slopes). Such residual effects tend to be much larger than the repeatable component of measured phenotypes in both laboratory and field settings, particularly for labile traits such as behavior, cognitive performance or hormone levels (Bell et al., 2009; Cauchoix et al., 2018; Fanson & Biro, 2019). As a consequence, standard models using raw trait values to calculate covzj,zk will tend to bias the magnitude of SRN effects for measured traits, i.e.…”
Section: Social Animal Modelsmentioning
confidence: 99%
“…For labile phenotypes such as behavior, hormones, and cognition, the magnitude of repeatable betweenindividual variation in measurements is generally modest in comparison to the total phenotypic variation observed across space and time (Bell, Hankison, and Laskowski 2009;Cauchoix et al 2018;Fanson and Biro 2015). This is unsurprising, given that these traits are often the primary mechanisms by which organisms can flexibly respond to ephemeral and stochastic variation in their local environments, such as by up-regulating circulating testosterone in response to social challenges (Eisenegger, Haushofer, and Fehr 2011), or by temporarily inducing a fear state in response to odor cues of predation (Mathuru et al 2012).…”
Section: Introductionmentioning
confidence: 99%